THE EFFECT OF FOREIGN DEBT, FOREIGN INVESTMENT AND INFLATION ON INDONESIA'S ECONOMIC GROWTH - Safrina; Jariah Abubakar (RADJA PUBLIKA, 2023)
The purpose of this study is to analyze foreign debt, foreign investment and inflation in Indonesia's economic growth using multiple linear regression analysis. The scope of this research spans 32 years (1990-2021). The regression tool in this study used eviews-9 software. The results showed that the foreign debt variable had a positive and significant effect on the condition of Indonesia's economic growth, the foreign investment variable had a positive and significant effect on Indonesia's economic growth and the inflation variable had no effect and was not significant on Indonesia's economy growth.